Risk of Acute Myocardial Infarction, Heart Failure, and Death in Migraine Patients Treated with Triptans. Issue 10 (5th October 2020) - Ghanshani, Serena; Chen, Cheng; Lin, Bryan; Duan, Lewei; Shen, Yuh‐Jer Albert; Lee, Ming‐Sum
Abstract : Objective: The goal of this study is to determine the strength of association between treatment with triptans and acute myocardial infarction, heart failure, and death. Background: Case reports in the literature have raised concerns over an association between treatment of migraine headaches with triptans and cardiovascular events. This study aims to systematically evaluate this association in a contemporary population‐based cohort. We hypothesized that triptan exposure is not associated with increased cardiovascular events. Methods: A retrospective cohort study was conducted within an integrated healthcare delivery system in Southern California. From January 2009 to December 2018, 189, 684 patients age ≥18 years had a diagnosis of migraine. In this group, 130, 656 were exposed to triptans. Patients treated with triptans were matched 1:1 to those not exposed to triptans by using a propensity score. The primary outcome was acute myocardial infarction; secondary outcomes were heart failure, all‐cause death, and combined acute myocardial infarction, heart failure, and death. Results: The incidence rate of acute myocardial infarction was 0.67 per 1000 person‐year in triptan‐exposed vs 1.44 per 1000 person‐year in not exposed patients. In propensity‐matched analyses, the adjusted hazard ratio for triptan exposure was 0.95 (95% confidence interval [CI] 0.84‐1.08) for acute myocardial infarction; 1.00 (95% CI 0.93‐1.08) for all‐cause death; 0.93 (95% CI 0.81‐1.08) for heart failure; and 0.99 (95% CI 0.93‐1.06) for a composite of acute myocardial infarction, heart failure, or death. Sensitivity analyses focusing on stratified subgroups based on age, gender, ethnicity, and several cardiac risk factors also revealed no significant association between triptan exposure and cardiovascular events. Conclusions: No association was found between exposure to triptans and an increased risk of cardiovascular events. These data provide reassurance regarding the cardiovascular safety of utilizing triptans for the medical management of migraine headaches.